Immune Microenvironment Signatures as Biomarkers to Predict Early Recurrence of Stage Ia-b Lung Cancer - Wang, Qiang; Zhou, Danting; Wu, Fang; Liang, Qingchun; He, Qiongzhi; Peng, Muyun; Yao, Tianyu; Hu, Yan; Qian, Banglun; Tang, Jingqun; Wang, Xiang; Liu, Wenliang; et al. (Frontiers in Oncology, 2021)
Introduction Approximately 30% of patients diagnosed with stage Ia-b NSCLC die of recurrent disease after surgery. This study aimed to identify immune-related biomarkers that might predict tumor recurrence in stage Ia-b NSCLC within 40 months after curative resection. Methods Gene expression data of stage Ia-b NSCLC samples was retrieved from the TCGA database, the GEO databases, and the Second Xiangya hospital (XXEYY) database. 22 types of tumor infiltrating immune cells and the expression of immune-associated genes were investigated using CIBERSORT, immunohistochemical staining, and GSEA analyses in total 450 patients (80 in training cohort and 370 in validation cohorts). Recurrence-related immune features were selected based on LASSO Cox regression model. Results High density of Treg cell and Macrophages M1 cell could be observed in recurrence group while the memory B cell were more frequently enriched in controls, yet Treg cells alone were significantly associated with tumor early recurrence (with an adjusted hazard ratio of 2.04, 95% CI 8.49-35.44). A handful of immune-related genes were identified in recurrence group. Based on Lasso regression analysis, the expressions of five immune-related genes, RLTPR, SLFN13, MIR4500, HYDIN and TPRG1 were closely correlated with tumor early recurrence. In training cohort (TCGA), the combination of these five genes has sensitivity and specificity of 85% and 85%, with AUC of 0.91 (95% CI 0.84-0.98) for lung cancer earlyrecurrence prediction, whereas in validation cohorts, the sensitivity and specificity using this panel was 61-89% and 54-82%, with AUC of 0.62-0.84. Conclusion Our study demonstrated that the immune microenvironment signatures were closely related to tumor early recurrence. Compared to tumor infiltrating lymphocytes, the expression of five immune-related genes could be robust biomarkers to predict early recurrence of stage Ia-b NSCLC after curative resection.